The role of phospholipase A2 in formation of anemia of inflammation in infants with acute bacterial diseases of respiratory organs - Pogribna, A. O. (Запорізький державний медичний університет, 2019)
Introduction: phospholipase A2 is a direct participant in the inflammatory reaction, which plays a significant pathogenetic role in the formation of anemia of inflammation due to the catalyzed removal of the fatty acid residue from phospholipids and causes their transformation into toxic compounds, the functioning of which leads to the dissolution of erythrocytes. It is known that extracellular phospholipids with a wide spectrum of specificity are found on the outer membrane of gram-negative bacteria and are involved in the release of bacteriocin toxin from the cell due to increased permeability of the membrane against the background of an increase in the level of lysophospholipids and fatty acids in the membrane. Aim: to study the role of phospholipase A2 in the formation of anemia of inflammation in infants with acute inflammatory bacterial diseases of the respiratory system. Matherials and methods: the main group included 10 children with anemia of inflammation acquired on the background of acute bacterial disease of the respiratory tract. The experimental group included 10 patients with iron deficiency anemia without related inflammatory diseases. The control group was represented by 10 conditionally healthy children. Studying groups were representative of the age and gender of children. The content of phospholipase in the blood serum of infants (mean age of patients was 1,4±0,4 years) was determined on immunoenzyme assay method using commercial kits Kit For Phospholipase A2 commercial kit. Lipoprotein Associated (LpPLA2). Statistical data analysis was performed using the statistical packages "EXCEL" and "Statistica 13.0" (StatSoftInc., JPZ8041382130ARCN10-J) with the calculation of the arithmetic mean (M), standard deviation (σ).
Keywords: тези доповідей